2008
DOI: 10.1002/dvdy.21503
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of vasotocin‐expressing cells in zebrafish: Selective requirement for the transcriptional regulators orthopedia and single‐minded 1 in the preoptic area

Abstract: The neurohypophysial peptide arginine vasotocin, and its mammalian ortholog arginine vasopressin, influence a wide range of physiological and behavioral responses, including aspects of sexual and social behaviors, osmoregulation, stress response, metabolism, blood pressure, and circadian rhythms. Here, we demonstrate that, in zebrafish (Danio rerio), the vasotocin precursor gene arginine vasotocin-neurophysin (avt) is expressed in two domains in the developing embryo: the dorsal preoptic area and the ventral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 64 publications
2
79
1
Order By: Relevance
“…Interestingly, Etv5b has a broad expression domain compared with where mature 5-HT cells are found, indicating that not only progenitors of the 5-HT population but also others express Etv5b. Next to the basal forebrain 5-HT cells, cells positive for avpl, oxtl, sst3 or TH1 are found (Dickmeis et al, 2007;Eaton et al, 2008;Filippi et al, 2010;Kaslin and Panula, 2001;. None of these markers was reduced in etv5b morphants, suggesting that etv5b has a different function in non-5-HT cells or that its function is compensated for by other factors.…”
Section: Etv5b Controls the Final Number Of 5-ht Neuronsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, Etv5b has a broad expression domain compared with where mature 5-HT cells are found, indicating that not only progenitors of the 5-HT population but also others express Etv5b. Next to the basal forebrain 5-HT cells, cells positive for avpl, oxtl, sst3 or TH1 are found (Dickmeis et al, 2007;Eaton et al, 2008;Filippi et al, 2010;Kaslin and Panula, 2001;. None of these markers was reduced in etv5b morphants, suggesting that etv5b has a different function in non-5-HT cells or that its function is compensated for by other factors.…”
Section: Etv5b Controls the Final Number Of 5-ht Neuronsmentioning
confidence: 97%
“…These markers outline neuroendocrine cell populations (Dickmeis et al, 2007;Eaton et al, 2008) Fig. 3H-X).…”
Section: Etv5b Plays a Unique Role In The Development Of Hypothalamicmentioning
confidence: 98%
“…In situ hybridization probes for otpa and otpb (Ryu et al, 2007), sim1a (Löhr et al, 2009), foxb1.2 , shh (Krauss et al, 1993), emx2 (Morita et al, 1995), nkx2.1a (Rohr and Concha, 2000), wnt8b (Kelly et al, 1995), fgf8 (Reifers et al, 1998), avpl (avp -Zebrafish Information Network) (Eaton et al, 2008), oxtl (oxt -Zebrafish Information Network) (Eaton and Glasgow, 2006), fgf3 (Maroon et al, 2002), arx (Miura et al, 1997), dlx2a (Akimenko et al, 1994), mcm5 (Ryu et al, 2005), pit1 (pou1f1 -Zebrafish Information Network) (Nica et al, 2004), prl, pomca (Herzog et al, 2003 and crabp1a (Liu et al, 2005) have been described. Probes for fezf2,lef1,lhx6,irx5a,gsx2,vip,uts1 and nr5a1a were PCR amplified using cDNA of 2-5 dpf embryos with the primers listed in supplementary material Table S2 and cloned into the pCRII vector.…”
Section: Probes In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
“…The function of hypothalamic regulators seems to have been highly conserved during evolution and zebrafish orthologs have similar roles to their mouse counterparts (Machluf et al, 2011). For example, zebrafish Otp and Sim1/Arnt2 are required for the development and function of neuroendocrine cells as well as for the development of diencephalic dopaminergic (DA) neurons (Amir-Zilberstein et al, 2012;Blechman et al, 2007;Del Giacco et al, 2006;Eaton and Glasgow, 2006;Eaton and Glasgow, 2007;Eaton et al, 2008;Löhr et al, 2009;Ryu et al, 2007). Zebrafish otpb is regulated by the zinc-finger protein Fezf2 (Blechman et al, 2007), which was originally identified as a factor upregulated by overexpression of Dkk1 in zebrafish (Hashimoto et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A part of specific gene expression of these four divisions is present in mammals, birds, reptiles, and amphibians. In the case of teleost fish, behavioral approaching (Portavella et al, 2004a(Portavella et al, , 2004bPortavella & Vargas, 2005) showed similar learning deficits after brain lesions on homologues areas to mammalian amygdala, and genetical studies showed constancy in the expression of pallial and subpallial genes, and the presence of, at least, a medial amygdala (Gonzalez & Northcutt, 2009) and the hypothalamical components (Eaton et al, 2008). The behavioral studies commented in previous sections of this chapter show how essential functions for species survival such as fear conditioning, escape and avoidance behavior, aggressive, and sexual behaviors are dramatically impaired after mammalian amygdala lesions, or homologues structures in the case of birds, reptiles, amphibians, or teleost fish (see sections II and III of this chapter).…”
Section: Resultsmentioning
confidence: 97%